2021
DOI: 10.52586/5049
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide signatures in flax pinpoint to adaptive evolution along its ecological gradient

Abstract: Background: Flax is one of the eight founder crops of agriculture. It is believed to have been domesticated as a long-day plant that has since spread to survive in a wide range of eco-geographic regions extending from the warm Indian subcontinent to the low latitude east African highlands and to the cool and high-latitude Eurasia. Understanding the genetic basis underlying its adaptation and selection events throughout its dispersion is essential to develop cultivars adapted to local environmental conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…The results of phylogenetic analysis of 385 materials from major flax producing areas in the world also showed that the clustering situation was not completely consistent with the flax source countries [28]. So we speculated that this is related to the different sources of the parent and maternal origin selected by each breed during breeding.For example, Baya 13 (GroupⅢ) from Hebei province, the mother selected during breeding is Jinya 7 from Shanxi province, also in GroupⅢ [44], So on the evolutionary tree these two varietise are in the same clade of GroupⅢ.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of phylogenetic analysis of 385 materials from major flax producing areas in the world also showed that the clustering situation was not completely consistent with the flax source countries [28]. So we speculated that this is related to the different sources of the parent and maternal origin selected by each breed during breeding.For example, Baya 13 (GroupⅢ) from Hebei province, the mother selected during breeding is Jinya 7 from Shanxi province, also in GroupⅢ [44], So on the evolutionary tree these two varietise are in the same clade of GroupⅢ.…”
Section: Discussionmentioning
confidence: 92%
“…Ahasanul et al [27] used 6,200 SNP markers to cluster 350 flax genotypes into 7 subpopulations (P1~P7) and considered that the wide geographic distance hindered gene flow. Demissew et al [28] used genome scanning and three SNP data sets to detect 385 germplasms from all major flax planting areas in the world. Through genome environment association analysis (GEA), they identified important SNPs on chromosomes 3, 7, 9 and 13 related to the temperature, day length and latitude of the planting season, which assisted flax breeding and genetic protection.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of diverse germplasm, characterization and evaluation data is of the greatest importance to realize the full potential of flax in agriculture [5] - [7]. Furthermore, plant breeders are continuously challenged to develop flax cultivars adapted to changing market needs and environments [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Current advances in genome technologies, and in computational and statistical methods in handling big data, have created opportunities to explore historical adaptive signatures and to reconstruct the past selection, hybridization, and other evolutionary events of several species [19,20], including those with complex genomes, such as wheat [18,21,22]. Genome scans, based on FST and principal components, have pinpointed genetic signatures of past selection and hybridization events, as well as the genomic regions underlying adaptation to environmental factors [23,24]. Using whole genome exome capture data, He et al [22] delimited a large introgression segment on chromosome 4A, between positions 174,725,311 and 485,745,837 bps, and postulated that its origin was wild emmer wheat.…”
Section: Introductionmentioning
confidence: 99%